Pharmaceutical Marketing: A Literature Review - Kalyani Rajput; Dr. Rajesh Kumar Pandey (International Journal of Engineering and Management Research, 2022)
Marketing is the essence businesses and the business fraternity globally have accepted this norm of marketing the products effectively in order to achieve desired results. One of the premier and global Industry is Pharmaceutical Industry. It has a wide range of scope right from over the counter (OTC) products to life savings drugs to medical equipments. So much so that Medical Education at large includes a separate section as Pharmaceutical Education and this premium education experiences builds the base for Pharma Product manufacturing. Getting across these products to the Market requires essential skills and hence it signifies the efforts of Pharmaceutical Marketing. As against the Marketing of general product, Pharma Marketing involves further more essentialities as it belongs to the category of useful & needy products but not desired products as one never plans in general to buy a medicine or medical equipment unless prescribed or advised under medical care. This factor poses the massive challenge in the field of Pharmaceutical marketing. The Review paper attempts to understand the essence & concept of Pharmaceutical Marketing. It further aims to massively review the existing literature on Pharmaceutical Marketing and present the inferences. This conceptual study is completed with the help of Secondary data. It encompasses the thoughts of authors & researchers who have contributed to the Pharmaceutical Marketing domain. The Review has been categorised into studies of Marketing Mix, Consumer Behaviour towards Pharma Products, Green Marketing approach and execution of Pharma Marketing. The Papers & literature reviewed have been selected on Author’s convenience & judgement, which may result in the limitation for study and the inferences presented may be indicative rather exhaustive.